Nikolakopoulou, Vasiliki - (:unkn) unknown (My University, 2026)
Born in Athens Greece, in 1987. Mathematics degree from the National and Kapodistrian University of Athens, specialized in Applied Mathematics with further specialization in Computational and Educational Mathematics. MSc in Design of Interactive and Industrial Products and Systems from University of Aegean (Syros, Greece). Volunteer research assistant at Mascil (Mathematics and Science for Life) research project, University of Athens, Greece. E-course developer for the e-learning platform Open Courses (Open Academic Courses at the University of Athens). Experienced and focused on a multidisciplinary approach in designing new technology applications for enhancing students’ learning of mathematics. Interest in re-using metadata enriched cultural assets in science and education, promoting culture through e-learning experiences, developing innovative methodologies for harvesting of massive and complex multimedia 3D/ 4D data sets. Other interests: gymnastics, sports, football, bass guitar.